Well-being, self-regulation, social support and sports recreation: Systematic review - Novoa López, Julio Alfonso; Hossein-Mohand, Hassan; De-Juanas Oliva, Ángel; Hossein-Mohand, Hossein; Díaz-Esterri, Jorge (Comparative Cultural Studies: European and Latin American Perspectives, 2025)
This study reviews the scientific literature on the relationship between participation in physical and sports activities and the psychological well-being of young people. Such activities foster self-acceptance, positive interpersonal relationships, and the development of a sense of purpose, while enhancing physical, psychological, and social skills. The research was conducted through a narrative systematic review, following the main methodological elements of the PRISMA statement. Academic databases were consulted, restricting the search to articles published in Spanish and English over the past five years. After a rigorous process of selection and exclusion, 17 scientific articles were analyzed. The reviewed studies were organized into several categories: the influence of the COVID-19 pandemic, health promotion, stress management, motivation for physical activity, and the role of social networks. The findings indicate that physical and sports activities help mitigate the negative effects of stress, enhance intrinsic motivation, and strengthen well-being. Moreover, social support emerges as a crucial factor in sustaining healthy behaviors and improving the youth experience in this field. The study concludes that physical activity is essential for comprehensive well-being. Future research should explore in greater depth the interactions between social support, demographic characteristics, and cultural factors to design more effective health promotion strategies.